CYTOTOXIC LABDANE DITERPENOIDS FROM ANDROGRAPHIS PANICULATA (BURM.F.) NEES - Tan, Maria Carmen s; Oyong, Glenn G; Shen, Chien-Chang; Ragasa, Consolacion Y (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The primary objective of this study was to probe the cytotoxic capacity of the labdane diterpenoids andrographolide (1), 14-deoxyandrographolide (2), 14-deoxy-12-hydroxyandrographolide (3), and neoandrographolide (4) on mutant and wild-type immortalized cell lines. Methods: Breast adenocarcinoma (MCF-7), colon carcinomas (HCT-116 and HT-29), small cell lung carcinoma (H69PR), human acute monocytic leukemia (THP-1), and wild-type primary normal human dermal fibroblasts - neonatal cells (HDFn) were incubated with 1-4, and the degree of cytotoxicity was analyzed by employing the in vitro PrestoBlueÂ® cell viability assay. Working solutions of 1-4 were prepared in complete cell culture medium to a final non-toxic dimethyl sulfoxide concentration of 0.2%. The plates were incubated at 37Â°C with 5% CO2 in a 98% humidified incubator throughout the assay. Nonlinear regression and statistical analyses were done to extrapolate the half maximal inhibitory concentration 50% (IC50). One-way ANOVA (p<0.05) and multiple comparison, Tukey's post hoc test (p<0.05), were used to compare different pairs of data sets. Results were considered statistically significant at p<0.05. Results: The highest cytotoxicity index was exhibited by the H69PR and 1 trials which displayed the lowest IC50 value of 3.66 Î¼g/mL, followed by HT-29 treated with 2, HCT-116 and 1 trials, and H69PR treated with 4 (IC50=3.81, 3.82, and 4.19 Î¼g/mL, respectively). Only 1 and 4 were detrimental toward MCF-7, while 1, 3, and 4 were degenerative against H69PR. Tukey's post hoc multiple comparison indicated no significant difference in the cytotoxicity of 1-4 on HCT-116 cells which afforded IC50 values ranging from 3.82 to 5.12 Î¼g/mL. Evaluation of the two colon carcinoma cell lines showed that HCT-116 was categorically more susceptible to cellular damage caused by treatments with 1-4 than was HT-29. Cytotoxicity was not detected in THP-1 and HDFn cells (IC50>100 Î¼g/mL). Conclusion: Diterpenoids 1-4 isolated from the dichloromethane extract of the leaves of A. paniculata exhibited different cytotoxic activities against MCF-7, HCT-116, HT-29, and H69PR. All constituents had comparable action on HCT-116 cells but were not found to be cytotoxic to normal HDFn cells and mutant THP-1 cells.